Antibacterial activity of selected australian syzygium species - G, Chikowe; L, Mpala; IE, Cock (Pharmacognosy Communications)
Introduction: Many species of Syzygium are known to have antiseptic activity. Australian Syzygium species had roles as traditional bush medicines for Australian Aborigines although their antiseptic potential has not been rigorously studied. Methods: Methanol extracts of leaves from Syzygium forte, Syzygium francissi, Syzygium moorei, Syzygium puberulum and Syzygium wilsonii were tested for antimicrobial activity by disc diffusion assay. Antibacterial strength was measured by MIC determination. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: S. forte, S. francissi, S. moorei, S. puberulum and S. wilsonii leaf methanolic extracts inhibited the growth of 5 (36%), 3 (21%), 3 (21%), 5 (36%) and 2 (14%) of the 14 bacteria tested respectively. Both Gram-positive and Gramnegative bacterial growth was inhibited by the Syzygium extracts, although Gram-positive bacteria appeared slightly more susceptible. With the exception of S. forte, all Syzygium leaf extracts tested also displayed low toxicity (LC50 > 1000 μg/ml) in the Artemia fransiscana bioassay. S. forte had a 48 h LC50 of 392.4 ± 33.0 μg/ml, making it slightly more toxic than Mevinphos (495.0 ± 35.1 μg/ml) and approximately 28 fold less toxic than potassium dichromate (14.0 ± 2.4 μg/ml) at 48 h. Conclusions: The antibacterial activity and low toxicity of the Syzygium spp. validate their medicinal usage by Australian Aborigines and indicate their potential as antibacterial medicinal agents.
Keywords: Syzygium forte; Syzygium francissi; Syzygium moorei; Syzygium puberulum; Syzygium wilsonii; Australian plants; medicinal plants; antibacterial